Epidemiology of Toxoplasma gondii infections in humans and selected wildlife and domestic animal species in an interface area in the Bushbuckridge Municipality, Mpumalanga, South Africa - Neves, Luís C.B.G. (University of Pretoria, 2024)
Thesis (PhD (Tropical Diseases))--University of Pretoria, 2022.